Reviewing Some Early Poverty Reduction Strategy Papers in Africa - Kende-Robb, Caroline (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2001)
This paper reviews some early interim and full PRSPs for countries with which the authors worked during 1999-2000 (Uganda, Burkina Faso, Tanzania, Mozambique, Mali and The Gambia). The purpose of the review is to compare and contrast how the PRSP process was established there. It finds that rapid progress was made in implementing the initiative in all the countries, increasing commitment to poverty reduction amongst government and donors and encouraging broader participation in the policy dialogue. However, there was considerable variation between the cases, reflecting different local contexts and capacities.